2019
DOI: 10.2139/ssrn.3481022
|View full text |Cite
|
Sign up to set email alerts
|

Generosity and Wealth: Experimental Evidence from Bogota` Stratification

Abstract: This paper combines laboratory experiments with a unique feature of the city of Bogotá to uncover the relationship between generosity and wealth. Bogotá is divided by law into six socioeconomic strata which are close proxies of household wealth and income. We recruit subjects from different strata and run a series of double-blind dictator games where the recipient is the NGO Techo-Colombia, which builds transitional housing for homeless families. We identify the stratum of each subject anonymously and blindly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…In line with recent evidence byBlanco and Dalton (2019) income does not seem to affect dictator game contributions as the impact of past revenues on dictator decisions can be precisely (at the 10% level) estimated at zero.…”
supporting
confidence: 86%
“…In line with recent evidence byBlanco and Dalton (2019) income does not seem to affect dictator game contributions as the impact of past revenues on dictator decisions can be precisely (at the 10% level) estimated at zero.…”
supporting
confidence: 86%
“…These data from a battery of real-world experiments lend more weight to the hypothesis that relative deprivation is negatively associated with generalized trust and prosociality. Several other studies have reported a similar pattern [34,[52][53][54][55][56][57][58][59][60][61]. In experimental settings, exposure to harsh environments has been associated with an increased willingness to defect in a Prisoner's Dilemma game, and a reduced tendency to send money to a partner in a Dictator Game [36,62,63], and experimentally induced financial deprivation can increase the willingness to cheat for financial rewards [64].…”
Section: Discussionmentioning
confidence: 64%
“…The picture is mixed. Some studies document a U-shaped relationship (Andreoni 2006a) and, in international rankings of generosity, both high-and low-income countries are ranked at the very top (Blanco and Dalton 2019). Other studies, however, find no relationship or a positive relationship with income or wealth (James and Sharpe 2007).…”
Section: Literaturementioning
confidence: 99%
“…Mahmud and Wahhaj (2018) empirically study voluntary contributions made by credit borrowers to their non-profit microfinance institute in Pakistan and report that clients donate more before they apply for another loan. In a laboratory experiment, Blanco and Dalton (2019) study charitable giving in Bogota by different social strata of individuals and conclude that the rich and poor are equally generous and both the rich and poor are similarly motivated, namely rather by warm-glow than by pure altruism. 3 Matching donations.…”
Section: Literaturementioning
confidence: 99%